2011
DOI: 10.1073/pnas.1107618108
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Hettinger: Olfaction is a physical and a chemical sense in Drosophila

Abstract: We would like to thank Dr. Hettinger (1) for his positive comment on our results showing that flies can discriminate isotopes by smell and are capable of cross-learning between odorants sharing a molecular vibration. Our article (2) demonstrated the presence of a physical (vibrational) component to odor character necessitating a vibration-sensing mechanism, the nature of which was not addressed experimentally and remains to be elucidated. We suggest that it likely involves inelastic electron tunneling, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Ligand-receptor interactions can be both attractive and repulsive, involving hydrogen bonding, van der Waals, cation-π, π-π, ion-ion, dipoledipole, steric, and hydrophobic interactions with the receptor, with water channels and bridging water molecules mediating hydrogen bonds, as well as metal-ion coordination, as we have recently demonstrated in the latter case (15,16). Therefore, molecular shape can be considered a "straw-man" alternative to the vibration theory when describing the differing affinities of ligands bound to GPCRs (17,18), including isotopomers (19,20). Some of these attractive and repulsive interactions were identified in 1940 by Pauling and Delbrück (21), who note that interacting biomolecules "must have complementary surfaces, like die and coin, and also a complementary distribution of active groups."…”
Section: Significancementioning
confidence: 98%
See 3 more Smart Citations
“…Ligand-receptor interactions can be both attractive and repulsive, involving hydrogen bonding, van der Waals, cation-π, π-π, ion-ion, dipoledipole, steric, and hydrophobic interactions with the receptor, with water channels and bridging water molecules mediating hydrogen bonds, as well as metal-ion coordination, as we have recently demonstrated in the latter case (15,16). Therefore, molecular shape can be considered a "straw-man" alternative to the vibration theory when describing the differing affinities of ligands bound to GPCRs (17,18), including isotopomers (19,20). Some of these attractive and repulsive interactions were identified in 1940 by Pauling and Delbrück (21), who note that interacting biomolecules "must have complementary surfaces, like die and coin, and also a complementary distribution of active groups."…”
Section: Significancementioning
confidence: 98%
“…In addition, shape-related features are misrepresented by vibration theory proponents. For example, Franco et al (17) stated: "Given that proteins are chiral, a shape-only theory cannot account for the identical odors of most enantiomeric pairs," echoing similar comments by Turin (22): "One would therefore generally expect enantiomers to have completely different smells. This is emphatically not the case."…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…However, the question of which vibrational band might be responsible for the ''deuterated'' character is difficult to answer at present. Our studies on Drosophila [28] have shown that fruit flies can generalize avoidance from a nitrile to a deuterated odorant of unrelated structure and vice versa. This is difficult to explain except by assuming that Drosophila perceives the <2150 cm-1 vibrational band, common to both, as having a distinctive odor.…”
Section: Discussionmentioning
confidence: 99%